Efektivitas Pembelajaran Matematika Realistik Terhadap Kemampuan Pemecahan Masalah Matematik Siswa Kelas VII SMP - Sinaga, Ananda Ria Pertiwi (CARTESIUS : Jurnal Pendidikan Matematika, 2018)
This study aims to (1) find out whether the mathematical problem-solving abilities of students who are taught by realistic mathematics learning were higher than those students who were taught using conventional learning; (2) knowing students' learning attitudes towards realistic mathematics learning approaches. This research is a quasi-experimental study with a quantitative approach. This research was conducted in class VII of the Junior High School 28 Medan 2017/2018 Academic Year where the population of this study was all class VII. Samples from this study were class VII-G as the experimental class and class VII-F as the control class. Based on the results of the analysis of calculations, the following data are obtained: (1) the results of analysis of realistic mathematical learning on students' mathematical problem-solving abilities using the t-test found that ttable = 1.68 and tcount = 3.6821 so tcount> ttable then concluded that H0 is rejected and Ha be accepted. The mathematical problem-solving abilities of students who are taught by realistic mathematics learning was higher than conventional learning. (2) student responses were very positive towards realistic mathematics learning with an average of â‰¥ 86.03.